Hybridization between beluga (Huso huso) and Persian sturgeon (Acipenser persicus) and their growth comparison - Pourkazemi, M.; Mohseni, M.; Nowruzfashkami, M.R.; Bahmani, M.; Taheri, A.; Yarmohammadi, M. (Iranian Fisheries Science Research Institute, 2007)
In order to evaluate the possible production of hybrids using two species of sturgeon; beluga (Huso huso) and Persian sturgeon (Acipenser persicus) a reciprocal crosses with three treatments and three replicates for each treatment was conducted. Reproduction normative including number of eggs per gram, fertilization rate, survival rate, and also 32 mophmetric and merestic parameters of parents, hybrids and control groups were compared. Genetic analysis of hybrid was conducted using two methods of cytogenetic (chromosome preparation) and molecular (microsatellite) techniques. Histological analysis was performed for sexual gonad development. The growth comparison between hybrids and control fish was conducted in fiberglass tanks for 18 months. Fish were fed using pellets and biometric measurements were carried out 17 times during the study period. Means, analysis of variance, standard deviation, Duncan s test and percentage of hetrosis were calculated using Quatro Pro and SPSS programs. Significant differences were detected between beluga controls and hybrids (male beluga x female A. persicus) and between A. persicus controls and hybrids (male beluga x female A. persicus) regarding number of eggs per gram (P 0.003). However no significant differences were detected between the control groups and hybrids regarding fertilization rate at the four celled and 35 celled stages, number of larvae produced, mortality rate up to the onset of exogenous feeding and the number of larvae surviving (P<0.01). Growth rates differed in hybrid fish and fish in the control groups and highest weight increase at the end of the rearing period belonged to beluga control (975±10 g) followed by hybrids produced by crossing female beluga with male A. persicus (840±143 g), hybrids produced by crossing female A. persicus with male beluga (681.85±281 g) and lowest growth increases belonged to the A. persicus control group (535.15±131 g). Specific growth rate in the second and third six months of rearing in hybrids produced by crossing female beluga with male A. persicus was higher than those recorded in the beluga control group. Percentage of hetrosis was negative during the early rearing period (-18.93), however at the end of the rearing period offspring were superior to parents and percentage of hetrosis was 0.79. Comparison of 32 morphologic and merestic parameters showed significant differences between 23 parameters between beluga controls and hybrids and between 31 parameters between A. persicus controls and hybrids (P,0.05). The hybrids production was proved using the cytogenetic (chromosomal count) as well as microsatellite techniques. The number of chromosomes in hybrids was intermediate to the parents (2n=190 ± 9) and like all other sturgeon species, microchromosomes comprised more than 50% of the chromosomes. The chromosome number in hybrids was half the number of chromosomes in the parents (A. persicus 2n=258±4 and beluga 2n=118±3). With regard to the fact that the number of chromosomes in A. persicus is 4N and that in beluga is 2N the number of chromosomes in hybrids is 3N or triploid. DNA bands produced by PCR in parents and offspring showed genetic inheritance. Histological analysis of control fish and hybrids after 18 months of rearing showed that male and female cells were observed in hybrids that is a characteristic feature of impotent or sterile fish. However only one type of sexual cells were observed in fishes in the control groups (A. persicus and beluga). Results obtained from the present study show that the hybrids produced are triploid (3N) and histologically sterile. Also hybrids produced showed good growth. With regard to the scarcity of female beluga and the limitation in the production of beluga fingerlings, it is suggested that sturgeon hatcheries produce hybrids and thus meet the fingerling demands of sturgeon farms. Also considering that the hybrids produced are sterile they can be considered as a candidate for export for aquarium fish. With regard to the fact that the hybrids produced are a new species it is suggested that this species is named Belupars which is a taken from the names of the two parents Beluga and Persicus.